A Prospective Study to Evaluate the SPY-QP Software for Intraoperative Perfusion Assessment in Breast Reconstruction - Hani I. Naga, MD; Jennifer Gallagher, BS; Joshua K. Kim, BS; Jenny Foster, BS; Yisong Geng, PhD, MBA; Nicholas C. Oleck, MD; Brett T. Phillips, MD, MBA (Plastic and Reconstructive Surgery, Global Open)
Background:. Laser-assisted indocyanine green angiography image quantification programs have been developed to guide the resection of ischemic tissue, but prior iterations have proved difficult to interpret. This study assesses outcomes using SPY-QP, a novel quantification algorithm of the SPY Portable Handheld Imaging system (Stryker Corporation). Methods:. A prospective study was designed to enroll patients who underwent breast reconstruction with implant-based or autologous techniques. A prospective database of patient demographics, operative details, and outcomes at 2-week, 1-month, and 3-month follow-ups were maintained. Postoperative skin necrosis, fat necrosis, and infection, among other metrics, were correlated with indocyanine green angiography relative values (%). Logistic regressions were conducted using R-Studio. Results:. Overall, 39 patients and 59 breasts were included in this study. Forty-nine (83.5%) breasts underwent implant-based reconstruction, whereas 10 (17.0%) were reconstructed with autologous tissue. Five (12.8%) patients had evidence of skin necrosis, 6 (15.4%) of fat necrosis, and 9 (23.1%) of postoperative infection. Of the patients with skin necrosis, 2 (40%) patients underwent local wound care, 2 (40%) patients required bedside debridement, and 1 (20%) patient required an operative debridement. Mean relative values were significantly lower in patients with skin necrosis in comparison to patients without skin necrosis (14.6%±12.4% versus 24.4%±13.4%, P < 0.05). For cutoff analysis, a 10% cutoff maximizes specificity, whereas a 36% cutoff maximizes sensitivity in this cohort. Conclusions:. The SPY-QP technology is highly specific at low values and can effectively guide surgeons in the resection of ischemic tissue. Conversely, it remains challenging to predict necrosis in gray zones.